PENGARUH AUDIT TENURE DAN PENERAPAN IFRS TERHADAP KETERLAMBATAN PENYAMPAIAN LAPORAN KEUANGAN DENGAN AUDIT REPORT LAG SEBAGAI PEMEDIASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Zuchrina Masyitah -; Tuti Meutia; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study aims to determine the effect of Audit Tenure and IFRS Implementation on Delay in Submission of Financial Statements with Audit Report Lag as Mediator. The annual report data of manufacturing sector companies listed on the Indonesia Stock Exchange for the 2011-2020 period is used as a sample in this study. This study uses purposive sampling technique in sampling so that a sample of 23 companies that meet the criteria are obtained. The research method used in this study is the binary logistic regression method, path analysis, and Sobel test which is assisted by using the SPSS application in carrying out data analysis techniques. The results in this study indicate that audit tenure has no effect on audit report lag, while the application of IFRS has an effect on audit report lag. The results also show that audit report lag affects the delay in submitting financial statements. In addition, audit tenure and the application of IFRS do not affect the delay in submitting financial statements. The results also show that audit tenure has no effect on delays in submitting financial reports through audit report lag, while the application of IFRS affects delays in submitting financial reports through audit report lag. The limitations of the study are that the dependent variable in this study is only seen in the categories of not being on time (late) and on time; Then, the object of research is a company that has experienced delays in submitting its financial statements, so there are several companies whose data are incomplete. Suggestions to further researchers, are expected to expand this research by adding other variables that have an influence, it is expected to use samples with companies from other sectors besides the manufacturing sector, then can use comparisons with samples of companies that experience delays and companies that have never experienced delays.